Expressão do colágeno tipo I e tipo III na banda anterior do ligamento glenoumeral inferior de fetos humanos - Chagas, Juliana Bastos Wilson (2018)
Glenohumeral dislocation is a frequent and disabling condition, affecting mainly young people, and has a significant stabilizer in the inferior glenohumeral ligament (LGUI). According to Neer, in recurrent shoulder dislocations, minor trauma causes a plastic deformity in the LGUI. The aim of this study is to obtain the expression of type I collagen that presents thicker, less uniform and less extensible fibers and type III that has thin, uniform and more extensible fibers in the anterior band of the inferior glenohumeral ligament in human fetuses without any alteration biomechanics. The composition of these collagens in the anterior band of the glenohumeral ligament was evaluated in four ligaments of human fetuses of gestational age ranging from 23 to 31 weeks. The ligaments were divided into three portions. Picrosirius red was used for histological study, and the images were measured by percentage of collagen area with reddish-yellow birefringence compatible with type I collagen and the whitish-green area relative to type III co-lange. Type I collagen was more frequent in all studied fields: In the portion I, near the humerus, presented a composition average of 77.20% while the composition of type III collagen presented a mean of 22.80%; in the intermediate portion II, presented a composition of type I collagen presented a mean of 74.89% and the collagen III a mean of 25.11% and in portion III, medial part of the ligament, a mean composition of 53.82% and type III collagen an average of 46.18%. The peripheral part, more proximal to the humerus, had a higher ratio between type I and type III collagens when compared to the medial part of the LGUI. In this way the peripheral part of the LGUI is more resistant and the medial portion more elastic. These results are in accordance with biomechanical work and reinforce Neer's theory. Keyword: Collagen. Fetuses. Inferior glenohumeral ligament.